ستخالص وتقدير الفعالية البيولوجية الوراق نبات الحسك Tribulus terrestris L - مقدود يسرى; لعمري نور الهدى (University of Eloued جامعة الوادي, 2024)
The aim of this study is to extract and estimate the biological effectiveness of the leaves of the Hasak plant, TRIBULUS TERRESTRIS L. The Hasak plant is a medicinal plant from the Tarataceae family that was harvested at the University of Shahid Hama Lakhdar in the El Oued Province in the month of December 2023, where the leaves of the plant were extracted with the following solvents: distilled water, Ethanol, a mixture of distilled water (30%) and ethanol (70%). We detected secondary metabolites of alkaloids, phenols, flavonoids and terpenes. After the extraction process, the yield of the aqueous extract showed the highest percentage, estimated at 18.55%. Through quantitative estimation of the total phenols and flavonoids of the extracts, the results showed that they contain a large amount of these compounds, as the highest amount of total phenols in the aqueous extract was EqAG mg\g) 580 As for the flanoids, the water + ethanol mixture extract contained the largest amount (490 EqAG mg/g). As for the antioxidant activity, it was estimated in two tests: the DPPH test and the FRAP test, where we found the largest value of the antioxidant activity in the water + ethanol mixture extract. Finally, the biological antibacterial activity was studied, where four strains of bacteria were tested at different concentrations. The results showed that the bacteria possessed resistance to some of the studied extracts.